Nanoconfinement: 1D Nanoconfined Ordered‐Assembly Reaction (Adv. Mater. Interfaces 8/2019). Issue 8 (23rd April 2019) - Liu, Shijie; Zhang, Xiqi; Jiang, Lei
Abstract : In article number1900104, Shijie Liu, Xiqi Zhang, and Lei Jiang summarize the recent advances in 1D nanoconfined chemical reactions. A new concept of ordered‐assembly reaction is proposed, by combining quantum‐confined superfluid with frontier molecular orbital theory, to understand the inherent mechanism of high‐performance 1D nanoconfined chemical reactions. The prospective of ordered‐assembly reaction is also presented.